1999
DOI: 10.1128/iai.67.1.421-422.1999
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Inhibition of Expression of Cysteine Proteinases Affects Entamoeba histolytica -Induced Formation of Liver Abscess in Hamsters

Abstract: Trophozoites of virulent Entamoeba histolyticatransfected with the antisense gene encoding cysteine proteinase 5 (CP5) have only 10% of the CP activity but retain their cytopathic activity on mammalian monolayers. In the present study we found that the transfected trophozoites with low levels of CP activity were incapable of inducing the formation of liver lesions in hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…In EHI_127670-silencing transfectants, a lower activity for EhCP-A1 and EhCP-A5 can be detected. This result supports the major role for these peptidases (especially EhCP-A5) in tissue destruction, as previously shown (25,26,34,35). However, it has not been possible to clarify which mechanism underlies the inhibition identified hererin.…”
Section: Discussionsupporting
confidence: 89%
“…In EHI_127670-silencing transfectants, a lower activity for EhCP-A1 and EhCP-A5 can be detected. This result supports the major role for these peptidases (especially EhCP-A5) in tissue destruction, as previously shown (25,26,34,35). However, it has not been possible to clarify which mechanism underlies the inhibition identified hererin.…”
Section: Discussionsupporting
confidence: 89%
“…The role of several CPs in the virulence of protozoan parasites, such as Trichomonas vaginalis (Alvarez-Sanchez et al, 2000), Leishmania major (Joshi et al, 2002), Trypanosoma cruzi (Tomas et al, 1997), Plasmodium vivax (Rosenthal et al, 1994) or E. histolytica (Ankri et al, 1999) has been conclusively demonstrated. Additionally, the functional versatility of CPs and the relevant role that they play in virulence make these molecules promising chemotherapeutic or vaccine targets (McKerrow, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In general, CPs participate in invasion of tissues by E. histolytica trophozoites (Reed et al, 1989b;Bruchhaus et al, 1996;Ankri et al, 1999). During invasion, CPs face different substrates in the host, mainly those forming the extracellular matrix, which may be degraded to allow the trophozoite invasion.…”
Section: Rehcp112 Degrades Collagen Type I Fibronectin and Destroys mentioning
confidence: 99%
“…Proteases have also been involved in E. histolytica virulence (Gadasi and Kessler, 1983;McKerrow, 1989;Keene et al, 1990;Reed et al, 1992;Tannich et al, 1992). There is experimental evidence demonstrating a direct correlation between virulence and rate of phagocytosis and protease activity (Orozco et al, 1985;Ankri et al, 1998;1999), but other reports contradict this assumption (Spice and Ackers, 1992;Montfort et al, 1993).…”
Section: Introductionmentioning
confidence: 99%